Four they are! Broadening the description of Mimosa flabellifolia (Leguminosae Mimosoideae), a rare species from the Brazilian Cerrado - Borges, Leonardo Maurici; Antar, Guilherme Medeiros (Phytotaxa, 2016)
During a recent floristic survey in the Jalapão region, located in the state of Tocatins, Brazil, the second collection of Mimosa flabellifolia, a species known only from the type material, was made. Since the type collection presents only fruits, we herein broaden the description of the species to include floral features. Knowledge about flower morphology, in particular the number of organs, confirms the placement of M. flabellifolia in the tetramerous M. ser. Paucifoliatae. Illustrations, notes and a discussion on issues related to Mimosa taxonomy and conservation in the Jalapão region are presented.